Performance Analysis Of Centrifugal End Suction Pump And Three Phase Induction Motor In The Distribution Pumping Station of PDAM Tirta Mountala, Aceh Besar Regency - Fathurrahman, Fathurrahman; Akbar, Habibi; Siregar, Ramdhan Halid; Utami, Rika Sri; Syukri, Mahdi; Fachri, Muhammad Rizal; Malahayati, Malahayati (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
This study evaluates the efficiency performance of the motor-pump system used by the regional water utility company to identify strategies for improving efficiency. The three-phase induction motor utilized is highly dependent on the quality of the supplied voltage. The primary focus of this research includes analyzing the efficiency performance of the system, examining the electrical parameters of the three-phase induction motor, which include voltage and current imbalance, power factor, and Specific Energy Consumption (SEC). Another focus is the optimization of the motor-pump system and estimating the potential energy savings and operational cost reductions achievable within one year. The research method involves measuring electrical and hydraulic parameters. Electrical parameters were measured using a 3-phase power analyzer (type DW-6195), which records current, voltage, frequency, power, and power factor. Hydraulic parameters were measured using an electromagnetic flow meter for flow rate readings, a manometer for pressure measurements, and a measuring tape to measure the water level in the reservoir tank. All measurement results were tabulated and further analyzed to evaluate the performance of electrical parameters and compare them to the hydraulic performance of the system. The results revealed that the efficiency of the PDAM motor-pump system is below 50%, indicating the need for a comprehensive system revitalization. An inspection of electrical parameters showed that voltage deviation is below 10%, voltage imbalance is below 5%, and current imbalance ranges between 5.65% and 7.35%. All electrical parameters comply with IEEE standards. The power factor, at 0.85, also meets electrical standards. The SEC value, below 0.44 kWh/m³, indicates potential energy efficiency. Based on the pump performance curve study, the pump system can be replaced with a pump unit that has a lower electrical power rating, reducing it from 75 kW to 55 kW, while maintaining its hydraulic performance. Implementing this revitalization is expected to save up to 172,800 kWh of energy per motor per year and reduce by 18.4%.